Some essays on utilitarianism - Seminar on "Utilitarianism and Beyond" (2011 : Department of Philosophy, University of Calcutta); Chattopadhyay, Uma; Jahan, Mahjabeen; Bhattacharyya, Pralayankar; University of Calcutta. Department of Philosophy (Kolkata : Department of Philosophy, University of Calcutta in Collaboration with Mahabodhi Book Agency, 2012)
Papers presented at a seminar held at Department of Philosophy, University of Calcutta from March 15-16, 2011.
"Under UGC SAP DRS (Phase-I) programme"--Foreword.
Includes bibliographical references.
Keywords: BENTHAM, JEREMY, -- 1748-1832.; MILL, JOHN STUART, -- 1806-1873.; UTILITARIANISM -- MORAL AND ETHICAL ASPECTS -- CONGRESSES; POLITICAL SCIENCE -- PHILOSOPHY -- CONGRESSES